2011
DOI: 10.4103/0256-4947.75780
|View full text |Cite
|
Sign up to set email alerts
|

How do medical students in their clinical years perceive basic sciences courses at King Saud University?

Abstract: BACKGROUND AND OBJECTIVES:The inclusion of detailed basic science courses in medical school curricula has been a concern of students. The main objective of this study was to explore the attitudes of medical students towards basic sciences courses taught to them in the preclinical years and the applicability of these courses to current clinical practice.DESIGN AND SETTING:A cross-sectional survey was conducted during 2008-2009 among medical students in their clinical years at King Saud University, Riyadh, Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
(9 reference statements)
2
33
0
1
Order By: Relevance
“…To support these finding, one study found that intrinsic motivation (intrinsic goal orientation) significantly associated with deep strategy use [7]. In line with other previous findings [7,33], this is typical of 1 st year medical students who are trying many ways of dealing with the perceived overloaded and difficult basic medical subjects [21][22][23]34]. …”
Section: Motivation and Learning Strategiessupporting
confidence: 68%
See 1 more Smart Citation
“…To support these finding, one study found that intrinsic motivation (intrinsic goal orientation) significantly associated with deep strategy use [7]. In line with other previous findings [7,33], this is typical of 1 st year medical students who are trying many ways of dealing with the perceived overloaded and difficult basic medical subjects [21][22][23]34]. …”
Section: Motivation and Learning Strategiessupporting
confidence: 68%
“…Certainly, according to the previous research on the learning of Anatomy done by Alam [22], and Ebomoyi, and Agoneyo [23], MBBS students experienced less hope in anatomy because they perceived the subject as difficult to understand and as the most overloaded subject in basic medical sciences. Conversely, in line with other previous studies on pharmacy and physiotherapy [22,23], this study reports that students enjoyed their respective lessons. As for MLS students, results on hope do correspond with the previous research.…”
Section: Students' Class-related Emotional Experiencesmentioning
confidence: 99%
“…These researchers found that students who experienced the new curriculums had a more positive attitude toward basic sciences than students in conventional classes. In addition, a study in Saudi Arabia explored medical students' attitude toward basic science courses that were taught in the preclinical years, and the applicability of these courses to current clinical practice (Alam 2011). In Japan, however, there has been only one study focusing on medical students' attitude toward basic sciences, and the subjects were limited to first-year students in one regional national medical school (Kitajima 2009).…”
mentioning
confidence: 99%
“…Results of several studies revealed that a great number of students believed that anatomy was taught with the traditional method and most of them were unable to remember what was taught during the preclinical phase (31,33). On the other hand, the results of Nabil et al demonstrated that 68% of the students strongly agreed about the importance of anatomy knowledge for their future role as physicians (25).…”
Section: Discussionmentioning
confidence: 82%